DOI: 10.25148/etd.fi13101566
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the effects of a school-based intervention on feelings of personal expressiveness in multi-problem adolescent youth

Abstract: investigation of the effects of a school-based intervention on feelings of personal expressiveness in multiproblem adolescent youth" (2005). FIU Electronic Theses and Dissertations. 1146.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Ferrer-Wreder et al Swenson (2004), also found a significant association between CLP participation and change in normative identity style, however, the reported change was in the negative direction Thus far, two YDP studies have evaluated the effect of the CLP intervention with a measure of affective identity exploration. Albrecht (2005) found that the association between participation in the CLP and feelings of personal expressiveness was significantly moderated by a gender by ethnicity interaction. Conversely, Albrecht 2007, in an application of structural equation modeling techniques, found that participation in the CLP was significantly associated with positive change in personal expressiveness relative to the control group without moderation by gender, ethnicity, or age.…”
Section: Conceptual Relations Between Cognitive and Affective Identitmentioning
confidence: 91%
See 3 more Smart Citations
“…Ferrer-Wreder et al Swenson (2004), also found a significant association between CLP participation and change in normative identity style, however, the reported change was in the negative direction Thus far, two YDP studies have evaluated the effect of the CLP intervention with a measure of affective identity exploration. Albrecht (2005) found that the association between participation in the CLP and feelings of personal expressiveness was significantly moderated by a gender by ethnicity interaction. Conversely, Albrecht 2007, in an application of structural equation modeling techniques, found that participation in the CLP was significantly associated with positive change in personal expressiveness relative to the control group without moderation by gender, ethnicity, or age.…”
Section: Conceptual Relations Between Cognitive and Affective Identitmentioning
confidence: 91%
“…This present outcome study was conducted as part of the Stage II evaluation of the CLP participatory transformative intervention approach in promoting both selfconstructive and self-discovery identity exploration in troubled adolescent youth. While previous studies have evaluated the CLP intervention in terms of self-construction processes (Ferrer-Wreder et aL., 2002;Swenson, 2004) or self-discovery processes (Albrecht, 2005(Albrecht, , 2007, no studies, to date, have evaluated the intervention in terms of both self-construction and self-discovery processes, nor have any studies examined the contemporaneous relationship between self-construction and self-discovery processes with troubled adolescent youth. The present study also examined potential exogenous contextual moderators of self-construction and self-discovery processes (i.e.…”
Section: Clp Stage 11 Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing research findings regarding indices conceptually linked to identity resolution are mixed (Albrecht, 2007). On the one hand, evidence suggests that psychosocial interventions can be effective in increasing identity exploration (crisis) and decreasing or loosening commitments with adolescents and with CLP participants in particular (Albrecht, 2005(Albrecht, , 2007Ferrer-Wreder et al, 2002) and that increases in self-discovery processing associated with participation in the CLP may be accompanied by an increase in identity distress (Albrecht, 2007). On the other hand, evidence also suggests that increases in perceived positive group support for the CLP counseling group members are associated with increasing resolution of identity conflict (Garcia, 2005).…”
Section: Developmental Challenge: Resolving Psychosocial Conflictmentioning
confidence: 99%